The Relationship between Awareness of HIV and AIDS Workplace Policy and Consultation on HIV and AIDS Policy Development among Staff of Moi University, Kenya - Nyang’ara, Naftal Michira (International Journal of Educational Studies, 2019)
The unprecedented effect of HIV and AIDS in Africa cannot be over-emphasized as it takes its toll mainly on the active age population of 15-49 years. This age group is the main workforce of any nation and, unfortunately, the most vulnerable to infection of HIV. There has been growing concern about the devastating impact of HIV and AIDS in many workplaces. In response, many universities have developed university specific HIV and AIDS policies for impact mitigation in the workplace. Moi University is a public institution with a large workforce hence targeted in the current study. Realizing the negative impact that HIV and AIDS has on workplaces and the importance of having an HIV and AIDS workplace policy, this study sought to determine the relationship between awareness of HIV and AIDS workplace policy and consultation on HIV and AIDS policy development among staff of Moi University. The study, whose main concern was about Moi University HIV and AIDS workplace policy, targeted teaching staff, non-teaching staff and senior management. To achieve this objective, the study used ex-post facto research design and stratified sampling technique in the selection of the study sample. A study sample made up of 330 participants was used for the study. The study utilized both qualitative and quantitative methods in data collection. These included Workplace Testing Questionnaire, document analysis and semi-structured interviews. Primary data was collected by use of self-administered questionnaires and interview schedules, while secondary data was collected from libraries. The study used the Statistical Package for Social Sciences (SPSS v 22.0) program to analyze the data collected. Qualitative data was analyzed thematically through coding. Both descriptive and inferential statistics were used. The descriptive statistics included frequencies and means. Correlation analysis was used to test hypotheses (to test the relationship between the independent and dependent variables). The findings revealed that Moi University had an HIV and AIDS workplace policy. It also emerged that lack of consultation on HIV policy development, was an impediment to successful implementation of the policy. The study concluded that HIV and AIDS workplace policy is a vital document in HIV and AIDS impact mitigation and, therefore, requires serious consultation among all employees of Moi University for purposes of ownership by every employee. Following this, the study recommended that consultation of all of all employees about HIV and AIDS workplace policy development be undertaken and worker’s views and opinion be considered when developing an HIV and AIDS workplace policy. The study is, therefore, expected to be of great significance to universities in addressing some of the HIV and AIDS workplace policy related implementation challenges.